2009
DOI: 10.1158/0008-5472.can-09-1567
|View full text |Cite
|
Sign up to set email alerts
|

Altered Runx1 Subnuclear Targeting Enhances Myeloid Cell Proliferation and Blocks Differentiation by Activating a miR-24/MKP-7/MAPK Network

Abstract: Disruption of Runx1/AML1 subnuclear localization, either by a single amino acid substitution or by a chromosomal translocation (e.g. t(8;21)), is linked to the etiology of acute myeloid leukemia (AML). Here we show that this defect induces a select set of micro-RNAs (miRs) in myeloid progenitor cells and AML patients with t(8;21). Both Runx1 and the t(8;21)-encoded AML1-ETO occupy the miR-24-23-27 locus and reciprocally control miR-24 transcription. miR-24 directly downregulates MAPK Phosphatase-7 and enhances… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
95
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 100 publications
(100 citation statements)
references
References 43 publications
5
95
0
Order By: Relevance
“…miR-24 has been recently implicated in various biological processes Lal et al, 2009;Zaidi et al, 2009;Qin et al, 2010) and has been reported to be regulated by TGF-b (Sun et al, 2008) and bone morphogenetic protein 2 (BMP-2; Sun et al, 2009). Regulation by miRNAs provides a means for cells to prevent the accumulation of certain proteins by blocking protein translation.…”
Section: Discussionmentioning
confidence: 99%
“…miR-24 has been recently implicated in various biological processes Lal et al, 2009;Zaidi et al, 2009;Qin et al, 2010) and has been reported to be regulated by TGF-b (Sun et al, 2008) and bone morphogenetic protein 2 (BMP-2; Sun et al, 2009). Regulation by miRNAs provides a means for cells to prevent the accumulation of certain proteins by blocking protein translation.…”
Section: Discussionmentioning
confidence: 99%
“…35 Its upregulation is caused by binding of the AML-ETO fusion product to the miR-24-23-27 gene locus. 35 MiR-24 inhibits the synthesis of mitogen-activated protein kinase phosphatase 7, thereby facilitating cell growth through activation of c-jun and p38 kinases in myeloid leukemia cells.…”
Section: Oncogenic Mirnasmentioning
confidence: 99%
“…35 Its upregulation is caused by binding of the AML-ETO fusion product to the miR-24-23-27 gene locus. 35 MiR-24 inhibits the synthesis of mitogen-activated protein kinase phosphatase 7, thereby facilitating cell growth through activation of c-jun and p38 kinases in myeloid leukemia cells. 35 MiR-125b and neighboring miRNA genes let-7c, miR-99a and miR-100 were aberrantly upregulated in TEL-AML1-positive ALL and different myeloid leukemias (Tables 1 and 2).…”
Section: Oncogenic Mirnasmentioning
confidence: 99%
See 1 more Smart Citation
“…While in other studies, it has been proved that miR-24 can inhibit the initial and progression of cancer cell [24,28,29]. Zaidi [40] reported that expression of miR-24 stimulated myeloid cell growth, rendered proliferation independent of interleukin-3 and blocked granulocytic differentiation. Qin [41] found that miR-24 regulates apoptosis by targeting FAF1 in cancer cells, which also suggested that miR-24 could be an effective drug target for treatment of hormone-insensitive prostate cancer or other types of cancers.…”
Section: Discussionmentioning
confidence: 98%